Applying models of scientific terms' surroundings in classification of scientific publications - Vaidas Balys; Rimantas Rudzkis (Lietuvos Matematikos Rinkinys)
This paper considers a problem of classification of scientific publications wich is treated here as a problem of finding keywords. Keywords are determined by making use of statistical analysis of distribution of scientific terms. Models of scientific terms surroundings – so called identification clouds – are presented as well as results of experiments of their applicability for keywords detection.